Uncovering Reflective Practices of Educators In Teaching and Learning Process: a Phenomenological Study from Elementary School in The Philippines - Eleanor Tandang Abelilla (Advanced Qualitative Research, 2024)
Recent PISA results consistently show that 15-year-old students in the Philippines are five (5) to six (6) years behind in critical competencies, including mathematics, science, and reading—issues that predate the pandemic. Given teachers' enormous influence on students' academic success, the efficacy of their teaching tactics is becoming increasingly important. The advent of the epidemic and adjusting to a new normal posed significant hurdles to established information transfer techniques. This study investigates the reflective practices of educators at Los Baños Central Elementary School, Philippines, analyzing the evolution of these practices across three key periods: pre-pandemic, during the pandemic, and in the post-pandemic "new normal." It further examines the integration of three distinct learning modalities employed during the 2020-2021 and 2021-2022 academic years. Additionally, the study emphasizes the importance of ongoing reflection by educators on their instructional methods to more effectively meet the needs of their students. Using a transcendental phenomenological methodology, the researchers conducted in-depth interviews with seven (7) educators, resulting in the identification and analysis of major themes in their responses. Through the data collection process, this study revealed that, despite numerous challenges encountered during the pandemic, educators effectively managed the crisis by engaging in reflective practices to enhance their teaching methods. The findings underscore the pivotal role of reflective practices in advancing the teaching-learning process and improving student academic performance.